THE TOURISM OF HEALTH IN BARRANQUILLA: JOINT STRATEGY BETWEEN THE HEALTH AND TOURISM SECTORS - Gutiérrez Peña, Adriana
The Productive Transformation Program, PTP (2010), proposes the development of health tourism, world-class sector, as a strategy of competitiveness and productivity in the country. This sector, integrates the theory of value chain that tends to create value for the customer, seeking to identify the sources of competitive advantage in those activities that generate value in a product or service. (Porter, 2013). Barranquilla is a city conducive to the Tourism of Health, for its wide range of medical services recognized, the rica hotel offer, gastronomic and tourist combined with competitive costs. On the basis of interviews is a qualitative analysis of the current state of Health Tourism in Barranquilla, their points of risk and its actors , identify other fields of action that share the sectors involved, define the gaps existing in the process of interaction, and the proposal of strategies that favor the articulation between the actors of the value chain of the Tourism of Health , which is reflected in higher quality in the attention, competitiveness, economic and social profitability for Barranquilla.